2012
DOI: 10.1590/s0034-737x2012000200001
|View full text |Cite
|
Sign up to set email alerts
|

Atmosfera controlada para o armazenamento de goiaba cultivar 'Paluma'

Abstract: Controlled atmosphere for storage of 'Paluma' guavaGuava is a highly perishable fruit. Controlled atmosphere (CA) storage techniques could extend its shelf life while maintaining the quality of fruit. The aim of this work was to determine the best CA conditions for the storage of 'Paluma' guava. The experiment consisted in a randomized block design with the follow treatments: [1] 20.9 kPa O 2 + 0.03 kPa CO 2 (CS -control); [2] 1.0 kPa O 2 + 2.0 kPa CO 2 ; [3] 2.0 kPa O 2 + 2.0 kPa CO 2 ; [4] 3.0 kPa O 2 + 2.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
0
7
2
3
Order By: Relevance
“…There was no significant difference in the soluble solid content of the fruit. The values obtained were higher than those from the same cultivar that were found by Souza et al (2010) in São Manuel, SP, Cavalini et al (2015) in Vista Alegre do Alto, SP, or by Brackmann et al (2012) in Santa Maria, RS (10.1, 8.6 and 7.7 °Brix, respectively). The titratable acidity after pruning on September 11 yielded the highest values (0.54 g 100 -1 citric acid), and those pruned in August 27 had the lowest titratable acidity (0.31 g 100 -1 citric acid).…”
Section: Daa Longitudinal Fruit Diameter (Mm) Transverse Fruit Diametcontrasting
confidence: 62%
“…There was no significant difference in the soluble solid content of the fruit. The values obtained were higher than those from the same cultivar that were found by Souza et al (2010) in São Manuel, SP, Cavalini et al (2015) in Vista Alegre do Alto, SP, or by Brackmann et al (2012) in Santa Maria, RS (10.1, 8.6 and 7.7 °Brix, respectively). The titratable acidity after pruning on September 11 yielded the highest values (0.54 g 100 -1 citric acid), and those pruned in August 27 had the lowest titratable acidity (0.31 g 100 -1 citric acid).…”
Section: Daa Longitudinal Fruit Diameter (Mm) Transverse Fruit Diametcontrasting
confidence: 62%
“…Brackmann et al (2012) found an increase in ascorbic acid during CA storage in 'Paluma' guava, but, in the present study, the opposite was observed: a reduction in ascorbic acid level after storage, being less significant under 5 kPa O 2 + 15 kPa CO 2 . Importantly, if 'Tupy' blackberry was stored in high O 2 partial pressure (10 kPa), the fruit showed 13.9 mg·100 g −1 of ascorbic acid; the fruit kept with low O 2 partial pressure (5 kPa) showed 25 mg·100 g −1 of ascorbic acid, which supports the CA use with low O 2 to supply blackberry to the market with high quality.…”
Section: Controlled Atmosphere Conditions For 'Tupy' Blackberry Storacontrasting
confidence: 88%
“…Probably the lowest respiration rate by fruit submitted to these two CA conditions has relation with the oxygen level employed in these conditions. In other fruits, some early studies verified a reduction in respiration rate with the O 2 partial pressure reduction (Gupta et al 2009;Brackmann et al 2012).…”
Section: Controlled Atmosphere Conditions For 'Tupy' Blackberry Storamentioning
confidence: 96%
See 1 more Smart Citation
“…Another key factor on storage is the gaseous concentration inside the chamber. The oxygen lowering and carbon dioxide increase further reduced the metabolism of fruit, extending the storage and shelf life (PERKINS VEAZIE & COLLINS, 2002;BRACKMANN et al, 2012). KADER (2002) recommended, for blackberries storage, an O 2 from 5 up to 10kPa and CO 2 from 15 up to 20kPa partial pressure, considering that high CO 2 partial pressure (>20kPa) reduced the ascorbic acid content (AGAR et al, 1997).…”
Section: Introductionmentioning
confidence: 99%